Respostas
respondido por:
2
Resposta:
Explicação passo-a-passo:
Verifique a igualdade abaixo é verdadeira:(
(y-6)2 = ( y-6) (y+6)
(y - 6)² = (y - 6)(y + 6)
(y - 6)(y - 6) = (y - 6)(y + 6) NÃO
(y - 6)(y - 6) ≠ (y - 6)(y + 6) diferente
PROVAR
(y - 6)(y - 6) = (y - 6)(y + 6)
y(y) + y(-6) - 6(y) - 6(-6) = y(y) + y(6) - 6(y) - 6(6)
y² - 6y - 6y + 36 = y² + 6y - 6y - 36
y² - 12y + 36 = y² 0 - 36
y² - 12y + 36 = y² - 36 FALSO
y² - 12y + 36 ≠ y² - 36 diferente
Perguntas similares
4 anos atrás
4 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás